Elevated plasma concentrations of lipoprotein(a) in medicated epileptic patients - Schwaninger, Markus; Ringleb, Peter A.; Annecke, Andrea; Winter, Ralph; Kohl, Brigitte; Werle, Egon; Fiehn, Walter; Rieser, Peter A.; Walter-Sack, Ingeborg (Journal of neurology, 2000)
Lipoprotein(a) [Lp(a)] has been identified as an independent risk factor for vascular diseases. There are no data on Lp(a) levels in patients on long-term medication with carbamazepine, phenytoin, phenobarbital, or valproate. To investigate the effects of such treatment on Lp(a) levels and common carotid artery intima media thickness we studied 51 epileptic outpatients on long-term antiepileptic medication and 51 age- and sex-matched controls. Lp(a) levels above 45 mg/dl were found in 11 of 50 patients, but in only 4 of 51 controls (P<0.05). The mean serum concentration of Lp(a) was 33.0±7.0 mg/dl in patients and 16.9±2.7 mg/dl in controls (P<0.05). Epileptic patients also had a thicker intima media of the common carotid artery (0.79±0.04 mm) than controls (0.69±0.02 mm, P<0.05) as measured by B-mode ultrasonography. Our results suggest an untoward effect of long-term antiepileptic medication on Lp(a) serum concentrations. Elevated Lp(a) levels might be a risk factor for arteriosclerosis in epileptic patients.
Gesehen am 28.03.2022